Integrating the CARTER and KANO Models to Enhance Customer Satisfaction - Marnoto Marnoto; Lukmandono Lukmandono (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
This research is motivated by the importance of improving customer satisfaction, a key to business success, particularly for wood pellet products. The study aims to integrate the CARTER and Kano methods to identify service and product attributes affecting customer satisfaction and assist in determining effective improvement priorities. A quantitative research method was used to collect data through questionnaires. The CARTER method assesses customer satisfaction dimensions such as compliance, assurance, reliability, tangibles, empathy, and responsiveness, while the Kano method classifies service and product attributes into must-be, one-dimensional, and attractive categories. The results show that integrating these two methods allows for effective categorization of attributes, enabling the company to focus on improving product and service quality. Fulfilling basic needs is crucial to avoid dissatisfaction, while performance and attractive needs contribute to higher customer satisfaction. The empathy and responsiveness aspects of service also significantly influence positive customer perceptions. Through the comprehensive and practical framework resulting from the integration of the CARTER and Kano methods, companies can enhance customer satisfaction sustainably while maintaining competitiveness in the wood pellet market